Does atopy affect the course of viral pneumonia? - (:unkn) unknown (ELSEVIER ESPANA SLU, 2018)
Background: The presence of atopy is considered as a risk factor for severe respiratory symptoms in children. The objective of this study was to examine the effect of atopy on the course of disease in children hospitalised with viral pneumonia. Methods: Children between the ages of 1 and 6 years hospitalised due to viral pneumonia between the years of 2013 and 2016 were included to this multicentre study. Patients were classified into two groups as mild-moderate and severe according to the course of pneumonia. Presence of atopy was evaluated with skin prick tests. Groups were compared to evaluate the risk factors associated with severe viral pneumonia. Results: A total of 280 patients from nine centres were included in the study. Of these patients, 163 (58.2%) were male. Respiratory syncytial virus (29.7%), Influenza A (20.5%), rhinovirus (18.9%), adenovirus (10%), human metapneumovirus (8%), parainfluenza (5.2%), coronavirus (6%), and bocavirus (1.6%) were isolated from respiratory samples. Eighty-five (30.4%) children had severe pneumonia. Atopic sensitisation was found in 21.4% of the patients. Ever wheezing (RR: 1.6, 95% CI: 1.1-2.4), parental asthma (RR: 1.5, 95% CI: 1.1-2.2), other allergic diseases in the family (RR: 1.8, 95% CI: 1.2-2.9) and environmental tobacco smoke (RR: 1.6, 95% CI: 1.1-3.5) were more common in the severe pneumonia group. Conclusions: When patients with mild-moderate pneumonia were compared to patients with severe pneumonia, frequency of atopy was not different between the two groups. However, parental asthma, ever wheezing and environmental tobacco smoke exposure are risk factors for severe viral pneumonia in children. (C) 2017 SEICAP. Published by Elsevier Espana, S.L.U. All rights reserved.
Keywords: Atopy; Children; Viral pneumonia; RISK-FACTORS; PNEUMOCOCCAL DISEASE; VIRUS/ALLERGEN INTERACTIONS; AIRWAY EPITHELIUM; CHILDREN YOUNGER; ASTHMA; INFECTIONS; IDENTIFICATION; EXACERBATIONS; EXPOSURE